The Development of Quality Evaluation Factor and Indicators for Dissertations of Faculty of Education, National University of Laos - DUANGPHACHANH, Phaivanh; SOUKHAVONG, Sithane; THALANGSY, Khamseng (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The objectives of study were to: 1) develop components and indicators for quality assessment of master's theses of the Faculty of Education, National University of Laos; 2) check the components and indicators of the quality assessment of the master's theses of the Faculty of Education, National University of Laos. The research method used the Delphi technique and the evaluation method using the Connoisseurship Model, which consists of 2 steps: Document analysis procedure to raise the draft elements and indicators and procedures to check the appropriateness of elements and indicators to assess the quality of Master's Theses. The target group of key informants are those who are qualified to be teaching and advisors for Master of Education theses. The tool used to collect data is the five-rating-scale itemized suitability assessment model. Statistics used in data analysis are: Median and Interquartile Range. The results of the study were as follows: The elements and indicators of the quality assessment of the Master's Theses of Faculty of Education, National University of Laos, after checking the appropriateness, consists of 10 elements and 91 indicators, namely: Element 1. The name of the research topic consists of 5 indicators; Element 2. The first element consists of 3 indicators; Element 3, Part 1 Introduction: 1) Background and importance, consisting of 7 indicators, 2) Research questions, consisting of 5 Indicators, 3) Objectives consisting of 4 indicators, 4) Scope of research consisting of 3 indicators, 5) Hypothesis consisting of 5 indicators, 6) Expected results consisting of 4 indicators. Element 4, Section 2 Review of documents and scope of thinking: 1) Review of theory and concepts consisting of 9 indicators, 2) Definition of terms in practice Consisting of 6 indicators. Element 5. Part 3 Scientific research methods, consisting of 7 indicators. Element 6. Part 4, Scientific research results and conclusions: 1) Results of research, consisting of 5 indicators, 2) Conclusions, consisting of 5 indicators. Element 7. Section 5, Conclusion, research limitations and recommendations, consisting of 9 indicators. Element 8, The abstract consists of 3 indicators. Element 9, references and appendices contain 4 indicators and Element 10, the style of writing a thesis, consists of 7 indicators.